Pengaruh Intellegence Quotient, Emotional Quotient, Spiritual Quotient, dan Tekanan Anggaran Waktu Audit Pada Perilaku Underreporting Of Time - Indrajaya, A. A.Ngurah; Astika, Ida Bagus Putra; Mimba, Ni Putu Sri Harta (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017)DO - 10.24843/JIAB.2017.v12.i02.P03, 2017)
ABSTRACT This study aims to explore the effect of the intellectual, emotional, spiritual and audit time of underreporting of time behavior. The method used in this study is explanatory research, which would explain the causal relationship between the four independent variables on the dependent variable. This study collected data through questionnaires. The population of this study are from public accountant auditors. This study used total sampling which used all population. While the data analysis includes descriptive analysis, the classical assumption test and verification analysis using Multiple Linear Regression Analysis. Based on the results of the analysis showed that Intellegence quotient, emotional quotient, spiritual quotient have a negative effect on underreporting of time behavior and audit time budget pressure have a positive influence on the underreporting of time behavior. The results showed that the level of Intellegence quotient, emotional quotient, spiritual quotient is high and the time budget pressure is low, the auditor will not do the underreporting of time behavior. Keywords : Underreporting of Time Behaviour, Intellectual Quotient, Emotional Quotient, Spiritual Quotient, Time Budget Pressure